Functional gene group analysis indicates no role for heterotrimeric G proteins in cognitive ability. - W David Hill; Christiaan de Leeuw; Gail Davies; David Cherry McLachlan Liewald; Anthony Payton; Leone C A Craig; Lawrence J Whalley; Mike Horan; William Ollier; John M Starr; Neil Pendleton; Danielle Posthuma; et al. (PLoS ONE)
Previous functional gene group analyses implicated common single nucleotide polymorphisms (SNPs) in heterotrimeric G protein coding genes as being associated with differences in human intelligence. Here, we sought to replicate this finding using five independent cohorts of older adults including current IQ and childhood IQ, and using both gene- and SNP-based analytic strategies. No significant associations were found between variation in heterotrimeric G protein genes and intelligence in any cohort at either of the two time points. These results indicate that, whereas G protein systems are important in cognition, common genetic variation in these genes is unlikely to be a substantial influence on human intelligence differences.